Wildbienen (Hymenoptera, Aculeata: Apiformes) des Mittleren Moseltals: Die Weinbausteillagen im Klotten-Treiser Moseltal - Krahner, André; Dathe, Holger H.; Schmitt, Thomas (Contributions to Entomology = Beiträge zur Entomologie, 2018)
In 2012 and 2013, the wild bee fauna of vineyards on steep slopes was investigated by means of hand-netting, pan traps and Malaise traps. A total of 3246 individuals was captured and identified, yielding 159 species of wild bees. Almost one third of the species registered is regarded as endangered or shows declining populations. Considering earlier results from nearby study sites, the results of this work underline the importance of steep slopes under viticultural management as (partial) habitats underlying the regional bee species richness.